2010
DOI: 10.1111/j.1574-6968.2010.02048.x
|View full text |Cite
|
Sign up to set email alerts
|

The methoxymalonyl-acyl carrier protein biosynthesis locus and the nearby gene with the β-ketoacyl synthase domain are involved in the biosynthesis of galbonolides in Streptomyces galbus, but these loci are separate from the modular polyketide synthase ge

Abstract: Galbonolides A and B are antifungal compounds, which are produced by Streptomyces galbus. A multimodular polyketide synthase (PKS) was predicted to catalyze their biosynthesis, and a methoxymalonyl-acyl carrier protein (methoxymalonyl-ACP) was expected to be involved in the biosynthesis of galbonolide A. Cloning of a methoxymalonyl-ACP biosynthesis locus (galGHIJK) and the flanking regions has revealed that the locus is colocalized with beta-ketoacyl synthase (KAS)-related genes (orf3, 4, and 5), but separated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 18 publications
(25 reference statements)
3
23
0
2
Order By: Relevance
“…It was previously shown that an inactivation of galI, one of the methoxymalonyl-ACP biosynthetic genes, selectively abolished GAL-A biosynthesis, whereas a vector-integrating gene disruption of galB dramatically reduced the level of GAL-A and -B (12). This galB disruption study implied that galA-E are involved in GAL biosynthesis; however, their biochemical roles remained veiled.…”
Section: Galbonolide (Gal)mentioning
confidence: 93%
See 4 more Smart Citations
“…It was previously shown that an inactivation of galI, one of the methoxymalonyl-ACP biosynthetic genes, selectively abolished GAL-A biosynthesis, whereas a vector-integrating gene disruption of galB dramatically reduced the level of GAL-A and -B (12). This galB disruption study implied that galA-E are involved in GAL biosynthesis; however, their biochemical roles remained veiled.…”
Section: Galbonolide (Gal)mentioning
confidence: 93%
“…The PCR-targeting mutagenesis method was used in the preparation of gene inactivation constructs (15). Intergeneric conjugation was used to introduce plasmids into S. galbus (12). Specifically, the conjugation experiment was started with the introduction of a gene inactivation construct into E. coli ET12567/pUZ8002.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations